2003
DOI: 10.1103/physrevb.68.075401
|View full text |Cite
|
Sign up to set email alerts
|

Bond formation at theNi/ZrO2interface

Abstract: We report on the formation of strong chemical bonds at the Ni(100)/cubic-ZrO 2 (100) polar interfaces. Ab initio density functional theory calculations demonstrate that both Zr/Ni and O/Ni junctions are energetically stable, and predict that two different interactions determine the interface adhesion. Our results reveal that O-Ni ionic bonds are formed by Ni electron donation, while the Zr-Ni bonds show a mixed character with ionic and electron hybridization contributions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
47
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 24 publications
5
47
1
Order By: Relevance
“…It is possible that not only the atomic and electronic structures but also the interfacial energy is different between Ni/ZrO 2 (001) and Ni/ZrO 2 (111) interfaces. According to recent theoretical studies, there are differences in the interfacial energies, which gives the actual stability of the each interface, between Ni(001)/ZrO 2 (001) 9) and Ni(111)/ZrO 2 (111) 5) interfaces, although the interface plane of Ni is different from each other. Furthermore, Beltrán et al reported that both the Zr-terminated and the Oterminated interfaces are energetically favorable in the Ni(001)/ZrO 2 (001) interface, 9) while Christensen and Carter reported that the O-terminated interface is energetically favorable in the Ni(111)/ZrO 2 (111) interface, 5) which is consistent with our result.…”
Section: Electronic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that not only the atomic and electronic structures but also the interfacial energy is different between Ni/ZrO 2 (001) and Ni/ZrO 2 (111) interfaces. According to recent theoretical studies, there are differences in the interfacial energies, which gives the actual stability of the each interface, between Ni(001)/ZrO 2 (001) 9) and Ni(111)/ZrO 2 (111) 5) interfaces, although the interface plane of Ni is different from each other. Furthermore, Beltrán et al reported that both the Zr-terminated and the Oterminated interfaces are energetically favorable in the Ni(001)/ZrO 2 (001) interface, 9) while Christensen and Carter reported that the O-terminated interface is energetically favorable in the Ni(111)/ZrO 2 (111) interface, 5) which is consistent with our result.…”
Section: Electronic Structurementioning
confidence: 99%
“…6,7) On the other hand, Beltrán et al reported that both the Zr-terminated and Oterminated interfaces are energetically favorable in the Ni(001)/ZrO 2 (001) interface. 8,9) In addition to the theoretical studies, several experimental studies have been carried out. Dickey et al studied the Ni/ZrO 2 interfaces, using Z-contrast imaging technique and EELS analysis, which were fabricated by reduction of the eutectic bonded NiO/ZrO 2 interface, and pointed out that the metallic bonding between Ni and Zr, which may be formed under the reduced atmosphere, is responsible for the stability of the Ni(111)/ZrO 2 (001) interface.…”
Section: Introductionmentioning
confidence: 99%
“…We use the SIESTA package [17] with basis sets formed by double-zeta polarized localized numerical atomic orbitals. More details about the conditions of the calculations can be found elsewhere [18]. …”
mentioning
confidence: 99%
“…The reduction peak in the TPR pattern at 306°C is attributed to the reduction of bulk NiO [33] while the reduction peaks at 420-450°C were related to NiO x species that are having strong interaction with ZrO 2 [29,34]. The strong interaction between the nickel metal and the zirconia could be probably due to an increased interfacial area [29,34]. While in the case of reductive precipitation catalysts, no significant consumption of hydrogen was observed in their TPR profiles which clearly indicates that the Ni is in its metallic state.…”
Section: Temperature-programmed Reduction Studiesmentioning
confidence: 99%
“…Presence of strong chemical bonds between the Ni metal and the ZrO 2 has been revealed based on a DFT calculation by Beltran [33]. The reduction peak in the TPR pattern at 306°C is attributed to the reduction of bulk NiO [33] while the reduction peaks at 420-450°C were related to NiO x species that are having strong interaction with ZrO 2 [29,34]. The strong interaction between the nickel metal and the zirconia could be probably due to an increased interfacial area [29,34].…”
Section: Temperature-programmed Reduction Studiesmentioning
confidence: 99%